Christology, Soteriology, and Ethics in John and Hebrews Collected Essays - Loader, William R.G. 1944- (Tübingen Mohr Siebeck, 2022)
Dieser Band versammelt Aufsätze zum Johannesevangelium und dem Hebräerbrief von William R. G. Loader. Sie erörtern, wie diese Schriften Jesus und seine Bedeutung darstellen und sich mit Kontinuität und Diskontinuität zur Tradition Israels auseinandersetzen sowie die ethischen Fragen ansprechen, die diese Schriften aufwerfen und auch evozieren.
This volume brings together essays on John and Hebrews by William R. G. Loader. Beside his monographs on John and Hebrews are numerous contributions to journals, conference volumes, and Festschriften, of which a representative selection is gathered here into a single volume. They discuss how these writings portray Jesus and his significance and deal with continuity and discontinuity with Israel’s tradition, as well as address the ethical issues which these texts raise and also evoke.
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Jesus Christ -- Person and offices; Jésus-Christ - Personne et fonctions; Jesus Christ; Bible; Bible; Bible; Bible; Salvation -- Christianity; Ethics in the Bible; Son of God; Son of Man; Wissenschaftliche Untersuchungen zum Neuen Testament; Salut - Christianisme; Morale dans la Bible; Fils de Dieu; Fils de l'homme; Christology; Ethics in the Bible; Salvation - Christianity; Gotteswort; Son of God; Son (of God); High Priest; Typology; Temple; Neues Testament; Son of Man; Array; Letter to the Hebrews; Noncompliance; Sacrifices; Aufsatzsammlung